Reducing stranded asset risk in off-grid renewable mine sites by including hydrogen production. (29th July 2022) - Jacob, Rhys; Müller, Michael
Abstract: Mine sites are an ideal candidate to be decarbonised through the installation of variable renewables and storage. However, the operation of mine sites is dependent on many factors, including mineral price, which can vary significantly, leading to periods of inactivity. Therefore, for sites that have invested in renewable generation and storage, there exists a potential of stranded assets, which negatively impact their business case, potentially reducing investment in such equipment and, therefore, decarbonisation potential. The current study therefore has investigated the potential of using variable renewable energy coupled with thermal energy storage and biodiesel to supply heat to a mine site. With the base case established, the economic impact of lower or no mine operations on the net present value were evaluated. To reduce the impact of mine turndown, the potential of installing a hydrogen production facility in an effort to utilise the stranded assets was also undertaken. Preliminary results show the base case to be very economical with a net present cost of $151.4 M after 30 operational years. This value was reduced to $45.7 M and -$81.1 M if the mine only operated at half capacity or did not operate at all, respectively. The addition of hydrogen production powered by the installed variable renewable generation resulted in a slightly better net present value of $174.7 M if the mine operated as normal for 30 years. For the two other cases, the installation of an electrolyser resulted in significantly better results than if it had not been installed for the half capacity and no operation cases with net present costs of $90.9 M and -$7.1 M, respectively. A sensitivity analysis on these results show that while the hydrogen production only plays a minor role in site savings, a price of between $1.1/kg to $2.0/kg is necessary for the system to be economically justifiable. Therefore, the current study shows that the addition of an electrolyser can significantly reduce the risk of stranded assets in fully renewable mine sites by providing an additional revenue stream during mine turndown events. Highlights: Mine sites are prime targets for decarbonisation however can have erratic production schedules. Hypothetical site in Geraldton, WA, found to be financially viable using renewable energy and storage. Periods of inactivity found to significantly reduce financial viability by 70–153%. Introduction of electrolyser significantly reduces financial impact of mine activity. Excess electricity falls from 43% to 3.5% with the installation of an electrolyser in the 'Full Demand' scenario.